Preparation method of basalt fiber SiO2 aerogel composite thermal insulation material
By using basalt fibers and silicon sol systems to prepare SiO2 aerogel composites, the problem of poor mechanical properties of SiO2 aerogel materials is solved, cost reduction and performance improvement are achieved, and it is suitable for high-demand thermal insulation applications.
Patent Information
- Application Number
- CN202411582803.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing SiO2 aerogel materials have poor mechanical properties, which are difficult to meet the needs of heat insulation materials in terms of high strength and toughness, and the commonly used reinforced fibers are costly and difficult to promote and apply.
Basalt fibers are used as the skeleton, and basalt fiber SiO2 aerogel composite material with high mechanical properties is prepared by casting molding, gel injection molding and freeze-drying. The bonding is short using silicon sol and agarose composite adhesive system. Fiber, combined with hydrophobic modification and graded drying, improves the mechanical properties of the material and thermal insulation properties.
The cost of composite materials is reduced, mechanical properties and thermal insulation properties are improved, and it is suitable for internal combustion engine exhaust systems and power batteries, with reduced thermal conductivity and enhanced applicability.
Smart Images

Figure CN119306470A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat-resistant materials, and in particular to a method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material. Background Art
[0002] SiO2 aerogel is a porous material composed of a three-dimensional nanoparticle skeleton and nanoscale pores. It has the characteristics of low density, high porosity, high specific surface area, low thermal conductivity and strong fire resistance. It has brought new development opportunities for traditional thermal insulation materials and is widely used in the construction field and transportation field (power batteries, exhaust pipes, etc.), such as SiO2 aerogel insulation felt, SiO2 aerogel insulation coating, SiO2 aerogel insulation mortar and SiO2 aerogel insulation concrete. Although SiO2 aerogel has many excellent properties, its mechanical properties are poor. In order to improve the mechanical properties of SiO2 aerogel, the usual method is fiber doping, using fiber as a reinforcing material to improve the mechanical properties of SiO2 aerogel products and ensure its excellent thermal insulation performance. Commonly used reinforcing fibers are mainly glass fiber, ceramic fiber, carbon fiber, etc.
[0003] Existing patent CN109019597A discloses a preparation method and application of cellulose / graphene oxide carbon aerogel, which comprises adding flax pulp to a precooled sodium hydroxide / urea aqueous solution to obtain a uniform cellulose solution, adding graphene oxide to mix, heating to gelate the solution, freeze-drying, and performing high-temperature carbonization treatment under a vacuum environment to obtain cellulose / graphene oxide carbon aerogel, which can be used as an electrode material and an adsorption material. However, the mechanical properties of the aerogel are poor, the specific surface area is small, and it is difficult to promote and apply.
[0004] The existing patent CN115108809B provides a method for preparing a modified silica aerogel thermal insulation composite material, using an organic silicon source and an inorganic aluminum source (ceramic fiber, aluminum silicate fiber, quartz fiber, etc.) as precursors, and adopting an acid-base two-step catalytic method to prepare a modified silica sol; the existing patent CN112830760B discloses a thermal insulation, high temperature resistant aerogel gradient composite material and a preparation method thereof, the aerogel gradient composite material uses ethanol and deionized water as solvents to fully dissolve the silicon source, and then uses an acid catalyst and inorganic fibers as fiber reinforcements, and obtains a gradient composite material final gel through a sol-gel, aging, and solvent replacement method, and finally obtains a thermal insulation, high temperature resistant aerogel gradient composite material through supercritical carbon dioxide drying treatment.
[0005] It can be seen that the above patents are mainly based on ceramic fiber, graphene fiber, high silica fiber, etc. as composite matrix, which is costly and difficult to promote. Basalt fiber is a natural and environmentally friendly material obtained by processing basalt. Its production process is short and produces almost no "three wastes". It has the lowest energy consumption in the production of all high-tech fibers (the energy consumption of basalt fiber is 1 / 16 of that of carbon fiber). It is a typical resource-saving and environmentally friendly green high-tech fiber. Basalt fiber has high strength, high modulus, high and low temperature resistance, chemical corrosion resistance, UV resistance, low moisture absorption, sound insulation, heat insulation, excellent environmental resistance and other performance characteristics. It has high comprehensive performance and cost performance, and can be widely used in civil engineering, transportation, energy and environmental protection, automobiles and ships, aerospace, petrochemicals, weapons and equipment and other fields.
[0006] SiO2 aerogel is a material with extremely high porosity and large specific surface area, which also leads to the low thermal conductivity of silica aerogel at room temperature and pressure. Such excellent thermal properties also make silica aerogel widely used in the field of thermal insulation materials. However, the extremely high porosity of silica aerogel also leads to its poor toughness and low mechanical strength, which also affects its application in the field of thermal insulation materials. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material, using basalt fiber as a skeleton and a casting molding method to prepare a basalt fiber SiO2 aerogel thermal insulation material that meets the thermal insulation requirements and improve the mechanical properties of the aerogel material.
[0008] The technical implementation scheme of the present invention is: a method for preparing a basalt fiber SiO2 aerogel composite insulation material, comprising the following steps: S1: making short basalt fibers into a basalt fiber skeleton preform with certain mechanical properties; S2: preparing SiO2 sol; S3: placing the fiber skeleton into the prepared SiO2 sol, aging, modifying, and graded drying to obtain a basalt fiber SiO2 aerogel composite material.
[0009] Preferably, the step S1: preparing the chopped basalt fibers into a basalt fiber skeleton preform having certain mechanical properties comprises the following steps:
[0010] S101 Basalt fiber pretreatment: The basalt fiber used is a basalt fiber without glue on the surface. Hexadecyl trimethyl ammonium chloride and distilled water are used to remove the residue on the fiber surface and improve the surface activity of the fiber. Put an appropriate amount of basalt fiber, hexadecyl trimethyl ammonium chloride and distilled water into an ultrasonic cleaner for 30 minutes, then put them into a magnetic stirrer and stir slowly for 1 hour, and finally take out the chopped fibers for cleaning, and repeat the cleaning four times. Put the cleaned chopped fibers into a glass dish and put them into a 60°C oven for drying.
[0011] S102 prepares a mixed solution: weigh silica sol, agarose and basalt short fibers according to the ratio, use 15%V excess distilled water, first pour silica sol, agarose and distilled water into a container, heat and stir in a water bath at 85°C until agarose is completely dissolved in water, then add the weighed basalt short fibers into the mixed solution, and fully stir the mixed slurry to ensure that the fibers do not agglomerate or settle. The ratio of silica sol to fiber is 8:1, and the mass fraction of agarose added is 1.68%.
[0012] S103 Gel injection molding and freeze drying: pour the mixed liquid in step S102 into a silicone mold, perform gel treatment in a 20°C water bath for 60 seconds, place the gelled basalt fiber embryos in a refrigerator and freeze for 12 hours, then take them out and place them in a freeze dryer and freeze-dry for 14 hours respectively.
[0013] S104 heat treatment: the basalt fiber body freeze-dried in step S103 is heat treated in a high-temperature lifting furnace at a temperature of 400° C. for 2 hours, and finally a basalt fiber porous skeleton block is obtained.
[0014] Preferably, the S2: preparing SiO2 sol comprises the following steps:
[0015] Gel synthesis: Prepare tetraethyl orthosilicate (TEOS), anhydrous ethanol (EtOH) and deionized water in a ratio of 1:6:4 and pour them into a container, then add hydrochloric acid solution, adjust the solution pH to 3-4, put the solution into a magnetic stirrer and slowly stir for 5 minutes, then slowly add the prepared deionized water, and stir for 3 hours at 65°C. Then add ammonia water to base-catalyze the silica sol, adjust the solution pH to 8-9, and then put it in a 40°C water bath to stand for gelation.
[0016] Preferably, the step S3: placing the fiber skeleton into the prepared SiO2 sol, aging, modifying, and drying in stages to obtain a basalt fiber SiO2 aerogel composite material comprises the following steps:
[0017] S301 gel aging: Place the fiber skeleton in the prepared SiO2 sol and age it in a muffle furnace for 24 hours, during which the aging temperature is maintained between 50°C and 70°C.
[0018] S302 Solvent replacement: Use solvent replacement agent to replace twice, each time for 12 hours.
[0019] S303 hydrophobic modification: trimethylchlorosilane / n-hexane mixed solution was used as the hydrophobic modifier with a volume ratio of 1:10. The modification was performed twice, each time for 12 hours.
[0020] S304 Normal pressure graded drying: Dry the modified material in step S303 in an oven at 60°C for 6 hours, at 80°C for 4 hours, and at 120°C for 4 hours.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) Using basalt fiber as the reinforcing matrix can reduce the cost of composite materials and facilitate mass production and application.
[0023] (2) The basalt fiber porous material was prepared by gel injection molding combined with freeze drying, and the silica sol-agarose composite adhesive system was used to bond the basalt short fibers to improve the mechanical properties of the composite material.
[0024] (3) The thermal conductivity of aerogel materials is further reduced, and the thermal insulation performance of composite materials is improved. It can be used in the fields of thermal insulation of internal combustion engine exhaust systems and thermal insulation of power batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a schematic diagram of the preparation process of basalt fiber SiO2 aerogel composite thermal insulation material.
[0026] Figure 2 This is a comparison chart of the thermal insulation performance of the material of the present invention and a certain product on the market. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] like Figure 1 As shown, the present invention provides a method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material, which specifically comprises the following steps:
[0030] S1: short chopped basalt fibers are made into a basalt fiber skeleton preform with certain mechanical properties;
[0031] S2: preparation of SiO2 sol;
[0032] S3: placing the fiber skeleton into the prepared SiO2 sol, aging, modifying, and graded drying to obtain a basalt fiber SiO2 aerogel composite material.
[0033] Wherein, S1: making the chopped basalt fibers into a basalt fiber skeleton preform with certain mechanical properties, comprising the following steps:
[0034] S101 Basalt fiber pretreatment: The basalt fiber used is a basalt fiber without glue on the surface. Hexadecyl trimethyl ammonium chloride and distilled water are used to remove the residue on the fiber surface and improve the surface activity of the fiber. Put an appropriate amount of basalt fiber, hexadecyl trimethyl ammonium chloride and distilled water into an ultrasonic cleaner for 30 minutes, then put them into a magnetic stirrer and stir slowly for 1 hour, and finally take out the chopped fibers for cleaning, and repeat the cleaning four times. Put the cleaned chopped fibers into a glass dish and put them into a 60°C oven for drying.
[0035] S102 prepares a mixed solution: weigh silica sol, agarose and basalt short fibers according to the ratio, use 15%V excess distilled water, first pour silica sol, agarose and distilled water into a container, heat and stir in a water bath at 85°C until agarose is completely dissolved in water, then add the weighed basalt short fibers into the mixed solution, and fully stir the mixed slurry to ensure that the fibers do not agglomerate or settle. The ratio of silica sol to fiber is 8:1, and the mass fraction of agarose added is 1.68%.
[0036] S103 Gel injection molding and freeze drying: pour the mixed liquid in step S102 into a silicone mold, perform gel treatment in a 20°C water bath for 60 seconds, place the gelled basalt fiber embryos in a refrigerator and freeze for 12 hours, then take them out and place them in a freeze dryer and freeze-dry for 14 hours respectively.
[0037] S104 heat treatment: the basalt fiber body freeze-dried in step S103 is heat treated in a high-temperature lifting furnace at a temperature of 400° C. for 2 hours, and finally a basalt fiber porous skeleton block is obtained.
[0038] Among them, the S2: preparation of SiO2 sol includes the following steps: preparing tetraethyl orthosilicate (TEOS), anhydrous ethanol (EtOH) and deionized water in a ratio of 1:6:4 and pouring them into a container, then adding hydrochloric acid solution, adjusting the solution pH to 3-4, placing the solution in a magnetic stirrer and slowly stirring for 5 minutes, then slowly adding the prepared deionized water, and stirring for 3 hours at 65°C. Then, adding ammonia water to base-catalyze the silica sol, adjusting the solution pH to 8-9, and then placing it in a 40°C water bath environment to stand for gelation.
[0039] Wherein, the S3: placing the fiber skeleton into the prepared SiO2 sol, aging, modifying, and graded drying to obtain a basalt fiber SiO2 aerogel composite material comprises the following steps:
[0040] S301 gel aging: Place the fiber skeleton in the prepared SiO2 sol and age it in a muffle furnace for 24 hours, during which the aging temperature is maintained between 50°C and 70°C.
[0041] S302 Solvent replacement: Use n-hexane as the solvent replacement agent, replace twice, and keep each time for 12 hours.
[0042] S303 hydrophobic modification: trimethylchlorosilane / n-hexane mixed solution was used as the hydrophobic modifier with a volume ratio of 1:10. The modification was performed twice, each time for 12 hours.
[0043] S304 Normal pressure graded drying: Dry the modified material in step S303 in an oven at 60°C for 6 hours, at 80°C for 4 hours, and at 120°C for 4 hours.
[0044] Example 2
[0045] like Figure 2 As shown, the basalt fiber aerogel composite felt prepared by the present invention has a water repellency of ≥99%, a compression rebound rate of ≥95%, a vibration mass loss of ≤0.5%, and a thermal conductivity of 0.018W / m·K at room temperature (25°C). The prepared basalt fiber aerogel composite felt is coated on the surface of a power battery for a temperature drop test and compared with a certain aerogel product on the market. The test steps are as follows:
[0046] (1) The surface of a power battery is coated with the material of the present invention and a commercial product respectively, and then placed in a temperature box respectively.
[0047] (2) Adjust the incubator temperature to 30°C and allow the battery to stand until the temperature reaches 30°C (estimated to stand for 4-8 hours).
[0048] (3) Adjust the incubator temperature to -30°C and maintain it for 24 hours.
[0049] (4) Record the average battery temperature data
[0050] The comparison chart obtained is as follows Figure 2 As shown, it can be seen that the thermal insulation performance of the material of the present invention is better, and the temperature drop rate of the power battery is significantly lower than that of another product.
[0051] The present invention prepares a basalt fiber skeleton with certain mechanical properties and low thermal conductivity by gel injection molding and freeze drying methods, and also introduces an organic binder agarose as a pore-forming agent, thereby increasing the porosity of the basalt fiber skeleton, improving the mechanical properties and thermal insulation properties, and can be widely used in the fields of thermal insulation of internal combustion engine exhaust systems, thermal insulation of power batteries, and the like.
[0052] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that changes may be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material, characterized in that: The following steps are involved: S1: short chopped basalt fibers are made into a basalt fiber skeleton preform with certain mechanical properties; S2: preparation of SiO2 sol; S3: placing the fiber skeleton into the prepared SiO2 sol, aging, modifying, and graded drying to obtain a basalt fiber SiO2 aerogel composite material.
2. The method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material according to claim 1, characterized in that: S1: making the chopped basalt fibers into a basalt fiber skeleton preform with certain mechanical properties, comprising the following steps: S101 Basalt fiber pretreatment: The basalt fiber used is a basalt fiber without glue on the surface. Hexadecyltrimethylammonium chloride and distilled water are used to remove the residue on the fiber surface and improve the surface activity of the fiber; S102 prepares a mixed solution: weigh silica sol, agarose and basalt short fibers according to the ratio, use 15%V excess distilled water, first pour silica sol, agarose and distilled water into a container, heat and stir in a water bath at 85°C until agarose is completely dissolved in water, then add the weighed basalt short fibers into the mixed solution, and fully stir the mixed slurry to ensure that the fibers do not agglomerate or settle. The ratio of silica sol to fiber is 8:1, and the mass fraction of agarose added is 1.68%; S103 Gel injection molding and freeze drying: pour the mixed liquid in step S102 into a silica gel mold, perform gelation in a 20°C water bath for 60 seconds, place the gelled basalt fiber embryos in a refrigerator and freeze for 12 hours, then take them out and place them in a freeze dryer and freeze dry them for 14 hours respectively; S104 heat treatment: the basalt fiber body freeze-dried in step S103 is heat treated in a high-temperature lifting furnace at a temperature of 400° C. for 2 hours, and finally a basalt fiber porous skeleton block is obtained.
3. The method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material according to claim 1, characterized in that: The step S3 specifically includes the following operations: S301 gel aging: put the fiber skeleton into the prepared SiO2 sol and age it in a muffle furnace for 24 hours, during which the aging temperature is maintained between 50℃ and 70℃; S302 solvent replacement: Use solvent replacement agent to replace twice, each time for 12 hours; S303 hydrophobic modification: trimethylchlorosilane / n-hexane mixed solution was used as the hydrophobic modifier, with a volume ratio of 1:10, and the modification was performed twice, each time for 12 hours; S304 Normal pressure graded drying: Dry the modified material in step S303 in an oven at 60°C for 6 hours, at 80°C for 4 hours, and at 120°C for 4 hours.
4. The method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material according to claim 3, characterized in that: The optimal aging temperature in step S301 is 60°C.
5. The method for preparing a basalt fiber SiO2 aerogel composite thermal insulation material according to claim 3, characterized in that: The solvent replacement agent is n-hexane.
Citation Information
Patent Citations
Basalt fiber thermal insulation decorative integrated plate and preparation method thereof
CN110357566A
Method for preparing silicon dioxide aerogel or composite product thereof
WO2023226710A1
Cited By
Microwave dielectric filter based on agarose-epoxy resin composite system and preparation method thereof
CN122026038A
Hard aerogel insulation felt with high water resistance and high mechanical property and preparation method thereof
CN122212662A